Comparison of three FLAIR vascular hyperintensities methodologies in patients with acute ischemic stroke. (June 2021) - Jing, Lina; Sui, Binbin; Shen, Mi; Qin, Haiqiang; Ke, Dena; Gao, Peiyi
Background: Multiple methods have been used to analyze fluid-attenuated inversion recovery (FLAIR) vascular hyperintensities (FVHs) which may represent collaterals in patients with acute ischemic stroke (AIS); however, there is no consensus between methods. Purpose: To compare three frequently used FVH methods for predicting early infarct volume and clinical outcome in patients with AIS. Material and Methods: Patients with AIS in middle cerebral artery territory were recruited. FVHs were evaluated using extensive FVHs, FVH-diffusion-weighted imaging (DWI) mismatch, and FVH-in/out-DWI. Infarct volume at baseline and day 7 were measured. Early neurological improvement (ENI) was assessed. Good outcomes were defined by modified Rankin Scale scores of 0–2 at 90 days. Results: Fifty-one patients were included. ENI was 55.6% in patients with extensive FVHs and 23.3% in those without ( P = 0.024). Patients with extensive FVHs had smaller infarct volume growth at seven days than those without ( P = 0.041). ENI was 48.3% in patients with FVH-DWI mismatch and 15.8% in those without ( P = 0.021). Patients with FVH-DWI mismatch had smaller infarct volumes at seven days than those without ( P = 0.038). Patients with FVH-out-DWI had smaller baseline infarct volumes, smaller seven-day volumes, and smaller infarct growth than those with FVH-in-DWI ( P <0.001, P <0.001, and P = 0.031, respectively). In multivariate logistic regression analysis, the infarct growth at seven days negatively independently predicted ENI (OR = 0.737, 95% CI 0.593–0.915, P = 0.006). However, none of the FVH classifications could predict a good 90-day outcome. Conclusion: Patients with extensive FVHs or FVH-DWI mismatch tend to have early favorable clinical outcome. FVH-out-DWI being associated with smaller infarct growth may also indicate early favorable clinical outcome.